Controversies in rheumatology: imaging of enthesitis in spondyloarthritis—does it mean anything for treatment decisions?. (25th February 2022) - Balint, Peter V; Poddubnyy, Denis
Abstract: Enthesitis is considered a hallmark manifestation of spondyloarthritis including axial spondyloarthritis and psoriatic arthritis. Detection of enthesitis might be challenging in both diagnostic and classification processes. In this debate, we discuss the controversy on the role of imaging in the detection of enthesitis including the relevance for treatment decisions in spondyloarthritis.